1722e Asbestos in latin america: present trends in production, consumption and policies. (24th April 2018) - Algranti, E; Ramos-Bonilla, JP; Terracini, B; Santana, V; Comba, P; Pasetto, R; Mazzeo, A; Cavariani, F; Trotta, A; Marsili, D
Abstract : Situation: Since asbestos has been banned in most industrialised countries, production and consumption have shifted to low and middle-income countries. At present, asbestos consumption in Latin America (LA) amounts to 10% of yearly global production. Brazil, the only LA producer, mined more than 7, 000, 000 tons of chrysotile between 1980 and 2013. Argentina, Chile, Honduras and Uruguay are the only LA countries where asbestos is banned and Brazil, Colombia and Mexico, the main consumers. The bulk of consumption is concentrated in asbestos-cement products. Use and health outcomes: In 2012 mortality from mesothelioma was in 5.6 and 1.0/1, 000, 000 in Argentina and Brazil, respectively. The few epidemiological studies available show clear evidences of clusters of mesothelioma in municipalities with a long history of asbestos consumption in Brazil and a forecast of rising incidence of mesotheliomas in Argentina and Brazil for the next decade. Employing a population attributable fraction method, a sizeable number of asbestos-related cancers was estimated for Argentina, Brazil, Colombia and Mexico. Policies and practices: The flawed arguments used by the industry to maintain its market, both to the public and in courtrooms, strongly rely on the lack of local evidences of ill effects and the invisibility of asbestos-related diseases in LA, due to limited number of studies and a difficult access of exposed workers to good quality health services. An inquiry made in Argentina, Brazil and Colombia disclosed only one internationally accredited laboratory for quantitative fibre analysis, doing only phase contrast microscopy. Proposals for future actions: In Brazil, non-governmental organisations of asbestos workers were pivotal to counter balance misinformation and inequities, ending recently in a Supreme Court decision to support eleven asbestos related state laws of prohibition, which, in practice, is curtailing asbestos mining. In parallel, continuous efforts should be made to stimulate the growth of competent and ethical researchers to convey adequate information to the scientific community and to the general public.